Distribution and haplotype associations of XPD Lys751Gln, XRCC1 Arg280His and XRCC1 Arg399Gln polymorphisms with nasopharyngeal carcinoma in the Malaysian population - Visuvanathan, Shaneeta (West Asia Organization for Cancer Prevention (WAOCP), APOCP's West Asia Chapter, 2014)
Background: DNA repair pathways play a crucial role in maintaining the human genome. Previous studiesassociated DNA repair gene polymorphisms (XPD Lys751Gln, XRCC1 Arg280His and XRCC1 Arg399Gln)with nasopharyngeal carcinoma. These non-synonymous polymorphisms may alter DNA repair capacity andthus increase or decrease susceptibility. The present study aimed to determine the genotype distribution of XPDcodon 751, XRCC1 codon 280 and codon 399 polymorphisms and haplotype associations among NPC cases andcontrols in the Malaysian population. Materials and Methods: We selected 157 NPC cases and 136 controls fromtwo hospitals in Kuala Lumpur, Malaysia for this study. The polymorphisms studied were genotyped by PCRRFLPassay and allele and genotype frequencies, haplotype and linkage disequilibrium were determined usingSNPstat software. Results: For the XPD Lys751Gln polymorphism, the frequency of the Lys allele was higher incases than in controls (94.5% versus 85.0%). For the XRCC1 Arg280His polymorphism, the frequency of Argallele was 90.0% and 89.0% in cases and controls, respectively and for XRCC1 Arg399Gln the frequency of theArg allele was 72.0% and 72.8% in cases and controls respectively. All three polymorphisms were in linkagedisequilibrium. The odds ratio from haplotype analysis for these three polymorphisms and their associationwith NPC was 1.93 (95%CI: 0.90-4.16) for haplotype CGC vs AGC allele combinations. The global haplotypteassociation with NPC gave a p-value of 0.054. Conclusions: Our study provides an estimate of allele and genotypefrequencies of XRCC1Arg280His, XRCC1 Arg399Gln and XPD Lys751Gln polymorphisms in the Malaysianpopulation and showed no association with nasopharyngeal cancer.